2015
DOI: 10.1128/aem.03315-14
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Carriage of Shiga Toxin-Producing Escherichia coli Serotypes O157:H7, O26:H11, O103:H2, O111:H8, and O145:H28 among Slaughtered Adult Cattle in France

Abstract: The main pathogenic enterohemorrhagic Escherichia coli (EHEC) strains are defined as Shiga toxin (Stx)-producing E. coli (STEC) belonging to one of the following serotypes: O157:H7, O26:H11, O103:H2, O111:H8, and O145:H28. Each of these five serotypes is known to be associated with a specific subtype of the intimin-encoding gene (eae). The objective of this study was to evaluate the prevalence of bovine carriers of these "top five" STEC in the four adult cattle categories slaughtered in France. Fecal samples w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
39
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 59 publications
11
39
0
1
Order By: Relevance
“…The eae-␥1 subtype was found in the serotype O157:H7 strain and the two serotype O145: H28 strains, while eae-␤1 was found in the four strains of serotype O26:H11 (isolated from shellfish and freshwater samples). These correlations are consistent with results obtained previously for strains belonging to the top five EHEC serotypes that were isolated from slaughtered adult cattle (11) and for strains linked to human diseases (51). These data are also consistent with publications that showed that the eae-␤ and eae-␥ subtypes were the two subtypes most frequently detected in clinical isolates associated with human infections (15,51,74).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The eae-␥1 subtype was found in the serotype O157:H7 strain and the two serotype O145: H28 strains, while eae-␤1 was found in the four strains of serotype O26:H11 (isolated from shellfish and freshwater samples). These correlations are consistent with results obtained previously for strains belonging to the top five EHEC serotypes that were isolated from slaughtered adult cattle (11) and for strains linked to human diseases (51). These data are also consistent with publications that showed that the eae-␤ and eae-␥ subtypes were the two subtypes most frequently detected in clinical isolates associated with human infections (15,51,74).…”
Section: Discussionsupporting
confidence: 92%
“…The main reservoir of STEC is cattle (11). However, other animals, such as sheep, goats, swine, birds, wild animals, and humans, can also harbor STEC strains in their digestive tracts (35)(36)(37).…”
mentioning
confidence: 99%
“…The cumulative prevalence (16.5%) of STEC O157 and top 6 non‐O157 STEC (O145, O103, O121, O111, O45 and O26) in the cattle surveyed was lower than previously recorded in a number of studies in the United States of America (USA) which reported prevalence rates ranging from 44.2% to 97.7% (Paddock et al, ; Stanford, 2016). Furthermore, studies that were carried out in Australia and France registered considerably lower prevalences of 7.7% and 1.8%, respectively, in cattle faeces (Bibbal et al, ; Mellor et al, ). However, the difference between the rate obtained in this study and previous studies in which far higher prevalence rates of the seven major STEC serogroups were observed may be mainly ascribed to differences in cattle populations surveyed.…”
Section: Discussionmentioning
confidence: 99%
“…Also, E. coli strain O157:H7 has been frequently isolated in dairy herds in the United States (34)(35)(36)58) and in other countries (14,39,65). It is known that young cattle harbor STEC at significant prevalence, often higher than that in adult cows (13,60,63,(65)(66)(67). Also, one study observed that soil and floor areas where calves were raised had a higher prevalence of STEC than areas housing adult cows (68).…”
Section: Discussionmentioning
confidence: 99%